A Deeper Understanding of Attitude and Norm Applicable to Green Hotel Selection - Wang, Lei; Shao, Yu-Xin; Heng, Jie-Yuan; Cheng, Yao; Xu, Ying; Wang, Zi-Xu; Wong, Philip Pong Weng* (Routledge, 2023)
The purpose of this study is to examine the relationships between three types of norms, two types of green purchase attitude, perceived behavioral control (PBC) and the intention to visit green hotels. An integrated theoretical framework was used in this study based on the theory of planned behavior (TPB). A total of 409 questionnaires were collected for analysis followed by subsequent empirical testing of the postulated hypotheses, which was performed using SPSS and AMOS. The results suggest that subjective norm positively influences personal norm, implicit attitude, explicit attitude, and intention. Personal norm, implicit attitude, explicit attitude, and PBC positively influence intention, respectively, while descriptive norm negatively influences intention. Furthermore, personal norm, implicit attitude, and explicit attitude were shown to partially mediate the relationship between subjective norm and intention to visit green hotels. This study expanded the TPB model by incorporating descriptive norm, intrinsic attitude, extrinsic attitude, and personal norm in the model to provide a better understanding of green hotel selection. The expanded TPB model will assist in clarifying the roles of the different types of attitudes and norms, and helps to determine the direct and indirect effect of each variable on customers’ decision to visit green hotels.